The therapeutic potential of triptolide and celastrol in neurological diseases - Cui, Yueran; Jiang, Xuejiao; Feng, Juan (Frontiers in Pharmacology, 2022)
Neurological diseases are complex diseases affecting the brain and spinal cord, with numerous etiologies and pathogenesis not yet fully elucidated. Tripterygium wilfordii Hook. F. (TWHF) is a traditional Chinese medicine with a long history of medicinal use in China and is widely used to treat autoimmune and inflammatory diseases such as systemic lupus erythematosus and rheumatoid arthritis. With the rapid development of modern technology, the two main bioactive components of TWHF, triptolide and celastrol, have been found to have anti-inflammatory, immunosuppressive and anti-tumor effects and can be used in the treatment of a variety of diseases, including neurological diseases. In this paper, we summarize the preclinical studies of triptolide and celastrol in neurological diseases such as neurodegenerative diseases, brain and spinal cord injury, and epilepsy. In addition, we review the mechanisms of action of triptolide and celastrol in neurological diseases, their toxicity, related derivatives, and nanotechnology-based carrier system.